Expanding educational opportunities or widening learning inequalities? Evidence from national reform of pre-primary education in Ethiopia. (4th May 2023) - Kim, Janice; Sabates, Ricardo
ABSTRACT: Since a nationwide reform of pre-primary education in 2010, Ethiopia has experienced a massive expansion of pre-primary enrolment that increased tenfold in six years. Our paper aims to assess the distribution of early literacy outcomes between children who attended preschool and those who did not and explore how that distribution has changed throughout the reform and by factors such as gender, location, and parental literacy. We find an overall increase in the achievement gaps associated with pre-primary participation between 2010 and 2016. There are also differential patterns in the learning gaps over the reform, with a particular disadvantage for rural students and a relative advantage for students with parents who are not literate. This study suggests that understanding a fuller picture of learning inequality is critical to designing policy to leave no one behind aligned with the UN Sustainable Development Goals.